Hypersingular integral equations for multiple interacting planar cracks in an elastic layered material under antiplane shear stresses - Ang, W.T.; Clements, D.L. (Elsevier Ltd., 1995)
A system of Hadamard finite-part singular (hypersingular) integral equations is derived for an antiplane elastic problem involving an arbitrary number of arbitrarily-located planar cracks in a tri-layered material. The equations are solved approximately to compute the stress intensity factors for specific eases of the problems.